Technology acceptance of zakat payment platform: An analysis of modified of unified theory of acceptance and use of technology - Erwanda Nuryahya; A. Jajang W. Mahri; Aas Nurasyiah; Fitranty Adiresuty (al-Uqud : Journal of Islamic Economics, 2022)
This study aimed to determine and analyse the factors that affect a zakat payer receiving and using the zakat platform to pay the zakat. A total of 264 self-administered questionnaires were distributed to respondents who have been paid zakat with the platform. The data were analysed using variance-based structural modelling (PLS-SEM) to examine the hypothesised relationships. The results show that performance expectations and social influence positively and significantly affect behavioural intentions. Facility conditions and behavioural intention have influenced positive and significant impacts on the behaviour of using the online zakat payment platform. Furthermore, this is caused by the trust of zakat payers against online zakat payment platforms that afford to pay zakat faster completion when compared to paying zakat offline. It is also supported by encouragement from the surrounding environment of zakat payers such as: family, work colleagues, community and charity organisations who use the online zakat payment platform.